2021
DOI: 10.3390/cells10123448
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Trabecular Meshwork Model for Pseudoexfoliation

Abstract: The lack of an animal model or an in vitro model limits experimental options for studying temporal molecular events in pseudoexfoliation syndrome (PXF), an age related fibrillopathy causing trabecular meshwork damage and glaucoma. Our goal was to create a workable in vitro model of PXF using primary human TM (HTM) cell lines simulating human disease. Primary HTM cells harvested from healthy donors (n = 3), were exposed to various concentrations (5 ng/mL, 10 ng/mL, 15 ng/mL) of transforming growth factor-beta1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…We recently demonstrated a decreased UPR clearance in XFG compared to earlier forms of the disease associated with increased TGF levels in all disease stages, which suggest the potential regulation of the autophagy pathway and TGF-autophagy cross-talk involved in cell repair and aggregate clearance [50]. Autophagy is an intracellular trafficking system that conveys cytosolic constituents to the lysosome for ensuing degradation, which is crucial for misfolded protein clearance, cell homeostasis by ubiquitin-proteasomal degradation, and cell repair [51][52][53][54][55].…”
Section: Autophagy and Mitochondrial Dysfunction And Protein Aggregat...mentioning
confidence: 94%
“…We recently demonstrated a decreased UPR clearance in XFG compared to earlier forms of the disease associated with increased TGF levels in all disease stages, which suggest the potential regulation of the autophagy pathway and TGF-autophagy cross-talk involved in cell repair and aggregate clearance [50]. Autophagy is an intracellular trafficking system that conveys cytosolic constituents to the lysosome for ensuing degradation, which is crucial for misfolded protein clearance, cell homeostasis by ubiquitin-proteasomal degradation, and cell repair [51][52][53][54][55].…”
Section: Autophagy and Mitochondrial Dysfunction And Protein Aggregat...mentioning
confidence: 94%
“…Informed consent was obtained from all patients who underwent standardized ophthalmic examination including slit-lamp examination, gonioscopy, and fundus biomicroscopy, and IOP measurement by Goldman applanation. The definitions of XFS/XFG are detailed elsewhere [1][2][3].…”
Section: Patient Recruitmentmentioning
confidence: 99%
“…Exfoliation glaucoma (XFG) is an age-related fibrillopathy characterized by protein deposits on various ocular surfaces. Transforming growth factor beta-1 (TGF-β1) has been shown to be increased in exfoliation syndrome (XFS) and XFG [ 1 , 2 ] eyes and is a key mediator for regulating extracellular matrix homeostasis [ 3 ], reactive oxygen species (ROS) production, and redox balance in the cell milieu [ 4 ]. ROS, in turn, induces/activates TGF-β1 and mediates many of the fibrogenic effects of TGF-β, forming a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified a link between elevated TGF-b2 levels in the AH and extracellular matrix (ECM) of patients with POAG (18)(19)(20)(21). It has been established that TGF-b isoforms regulate TM cellular fate due to their mesenchymal nature (22)(23)(24), with a heightened presence of TGF-b2 stimulating a myofibroblast phenotype, increasing contractile features, profibrotic protein expression (a-SMA, fibronectin) and ECM deposition (25,26). Overall, these factors contribute to a loss of cell-cell contact, increased stiffness, and fibrosis of the TM, leading to AH outflow resistance and increased IOP (26).…”
Section: Glaucoma Pathophysiologymentioning
confidence: 99%